Innovation behavior of small and medium enterprises in the Philippines - Lim, Cristina Teresa Natividad (Animo Repository, 2022)
Due to the emergence of technology, there has been a rapid transformation of the way things are done as a result of digitalization innovation for small and medium enterprises (SMEs) in the Philippines to remain competitive. The purpose of this study is to present an overview of innovative behavior and perception among SMEs surveyed from the 2015 World Bank Enterprise Survey and from the 2015 Survey of Innovation and Activities of Establishments for the Philippines. Analysis of the innovation components such as product innovation, process innovation, and mapping of the main innovative activities was examined. The results showed that SMEs spend less on formal research and development and have less purchase or license of any patented or non-patented inventions. Moreover, SMEs provide less formal training to any of its employees specifically for the development and/or introduction of new or significantly improved product services and processes. Innovation showed a negative covariance which means that innovation and R&D expenditures tend to move in inverse directions. This situation should allow the government to come up with national policy interventions that support and encourage innovation especially for the SMEs.